Correction to: Sexual and reproductive health (SRH): a key issue in the emergency response to the coronavirus disease (COVID- 19) outbreak - Kun Tang; Junjian Gaoshan; Babatunde Ahonsi; Moazzam Ali; Mercedes Bonet; Nathalie Broutet; Edna Kara; Caron Kim; Anna Thorson; Soe Soe Thwin (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.